Small-Diameter PTFE Portosystemic Shunts: Portocaval vs Mesocaval. Issue 6 (1998) - Shields, Robert
Abstract : Fifty-seven patients with failed sclerotherapy received a mesocaval interposition shunt with an externally supported, ringed polytetrafluoroethylene prosthesis of either 10 or 12 mm diameter. Thirty-one patients had Child-Pugh gradeA disease and 26 grade B; all had a liver volume of 1000– 2500 ml. Follow-up ranged from 16 months to 6 years 3 months. Three patients (5 per cent) died in the postoperative period. There were two postoperative recurrences of variceal haemorrhage and one recurrent bleed in the second year after surgery. The cumulative shunt patency rate was 95 per cent and the incidence of encephalopathy 9 per cent; the latter was successfully managed by protein restriction and/or lactulose therapy. The actuarial survival rate for the whole group at 6 years was 78 per cent, for those with Child-Pugh grade A 88 per cent and for grade B 67 per cent. Small-lumen mesocaval interposition shunting achieves portal decompression, preserves hepatopetal flow, has a low incidence of shunt thrombosis, prevents recurrent variceal bleeding and is not associated with significant postoperative encephalopathy.